Marine Pollution Crisis (IntechOpen, 2026)
Marine Pollution Crisis – Understanding Impacts and Innovating Solutions examines one of the most pressing environmental challenges of our time: the escalating threat of marine pollution and its far-reaching consequences for ecosystems and human societies. Drawing on multidisciplinary perspectives, the book offers a compelling synthesis of the key types of marine pollutants—ranging from microplastics and heavy metals to nutrient runoff—and critically examines their impacts on biodiversity, fisheries, and coastal communities. With a global outlook and regional case studies, the volume highlights the interconnectedness of ocean health and sustainable development. Readers will discover discussions on environmental monitoring, socio-economic vulnerability, pollution governance, and adaptation strategies in response to climate change. The book’s strength lies in its integrative approach, combining environmental science, policy analysis, and sustainability thinking to propose practical pathways for mitigating marine pollution. Ideal for researchers, students, policymakers, and practitioners in marine science, environmental studies, and resource management, this edited volume provides valuable insight into marine environmental sustainability, climate-resilient coastal livelihoods, and evidence-based decision-making. It makes a meaningful contribution to the ongoing global discourse on sustainable oceans, making it a timely and essential resource for those committed to protecting marine ecosystems and promoting the health of our planet.